2011
DOI: 10.1021/la1049259
|View full text |Cite
|
Sign up to set email alerts
|

The Accelerated Late Adsorption of Pulmonary Surfactant

Abstract: Adsorption of pulmonary surfactant to an air−water interface lowers surface tension (γ) at rates that initially decrease progressively, but which then accelerate close to the equilibrium γ. The studies here tested a series of hypotheses concerning mechanisms that might cause the late accelerated drop in γ. Experiments used captive bubbles and a Wilhelmy plate to measure γ during adsorption of vesicles containing constituents from extracted calf surfactant. The faster fall in γ reflects faster adsorption rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The proteins greatly accelerate the adsorption of the lipids, which by themselves adsorb slowly and incompletely. 17 Adsorption reduced surface tension to 23.6 ± 0.3 mN/m, well below the onset of collapse.…”
Section: Resultsmentioning
confidence: 94%
“…The proteins greatly accelerate the adsorption of the lipids, which by themselves adsorb slowly and incompletely. 17 Adsorption reduced surface tension to 23.6 ± 0.3 mN/m, well below the onset of collapse.…”
Section: Resultsmentioning
confidence: 94%
“…In addition to the molecular mechanisms previously proposed, PE could also act in vivo by modifying the biophysical properties of surfactant. Rapid adsorption of lipids to the air-liquid interface is an essential property of lung surfactant and the hydrophobic surfactant proteins SP-B and SP-C play a crucial role in this effect but recently it has been reported that PE also induces acceleration in the adsorption rate [ 34 , 35 ]. In other experiments, aerosolized nanovesicles prepared with DPPC and dioleylphosphatidylethanolamine improved the resistance of pulmonary surfactants to inhibition in mice with acid-induced lung injury [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…With a clean interface, devoid of a film, the high surface tension can drive adsorption of vesicles containing only lipids. 4 Approaching the equilibrium spreading tension, adsorption requires the proteins. 4 …”
Section: Introductionmentioning
confidence: 99%